Enhancing TPACK: Preservice mathematics teachers' experiences with digital and non-digital visualisation tools - Ngwabe, Abongile; Boateng, Sakyiwaa (Journal of Education and e-Learning Research, 2025)
This paper investigates how pre-service mathematics teachers interact with both digital and non-digital tools to visualize mathematical concepts and develop their technological pedagogical content knowledge (TPACK). Based on the TPACK framework, this study explores how preservice mathematics teachers (PSMTs) transformed their teaching approaches when visualization tools were adopted, along with the respective challenges and affordances involved. An interpretivist qualitative phenomenological design was employed, which included semi-structured interviews, reflective journals, and pre- and post-microteaching observations of six third-year Bachelor of Education students. The intervention focused on delivering graduate-level mathematics content using GeoGebra and physical manipulatives. Results demonstrate a significant difference in PSMT’s technological knowledge (TK), technological pedagogical knowledge (TPK), and technological content knowledge (TCK) before and after the intervention. Participants teaching practices shifted from from being traditional, teacher-centered to modern, student-centered approaches. Challenges such as limited technical proficiency and infrastructural barriers were initially evident; however, exposure and support during the intervention improved confidence, tool fluency, and pedagogical adaptability. The study emphasizes the importance of embedding a TPACK-based teaching approach into mathematics teacher training programs to enhance PSMTs readiness for technology-integrated instruction. Consequently, the study contributes to the growing scholarship on visualization in mathematics education and highlights the pedagogical shifts necessary to prepare future teachers for 21st-century learning environments.